Monetary Policy, Inflation Illusion and the Taylor Principle: An Experimental Study - Wolfgang Luhan; Johann Scharler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
We develop a simple experimental setting to evaluate the role of the Taylor principle, which holds that the nominal interest rate has to respond more than one-for-one to fluctuations in the inflation rate. In our setting, the average inflation rate fluctuates around the inflation target if the computerized central bank obeys the Taylor principle. If the Taylor principle is violated, then the average inflation rate persistently deviates from the target. We find that these deviations from the target are less pronounced, if inflation rates cannot be as readily observed as nominal interest rates. This result is consistent with the interpretation that subjects underestimate the influence of inflation on the real return to savings if the inflation rate is only observed ex post.
Keywords: E30; E52; C90; 330; Taylor principle; Interest Rate Rule; Inflation Illusion; Laboratory Experiment